Jordan Economic Monitor, Fall 2020 : Navigating through Continued Turbulence - World Bank (World Bank, Washington, DC, 2021)
The global economy continues to reel from the COVID-19 (coronavirus) shock. The initial economic impact of COVID-19 on global output is projected to be far more devastating than the disruptions observed during the peak downturn of the global financial crisis of 2007–09. Across theworld, lockdowns and mobility restrictions meant to control the spread of virus caused a significant slump in consumer spending and production during the first half of 2020. This in turn created substantial challenges for labor markets worldwide and has led to widespread layoffs. In addition to the economic cost, however, the pandemic has also inflicted an irreversible cost to economies in the form of human loss. So far, estimates indicate that over one million humans have lost their lives worldwide, while millions more still battle the pandemic. Beside its impact on human life, the COVID-19 pandemic has wide ranging socio-economic impacts, endangering lives, livelihoods, employment, and earnings as well as impeding service delivery. According to World Bank estimates, the pandemic could also lead to permanent loss in learning resulting in trillions of dollars in lost earnings. Despite the challenging conditions, recent global economic information indicates some recovery, albeit uneven and possibly temporary,across countries after gradual easing of lockdowns. This recovery, which is largely supported by unprecedented interventions by the central banks and governments, however, remains uneven and still far from the pre-pandemic levels. In particular, most of the major economies are again observing a surge in new infections and some of them have already re-instituted targeted lockdowns. This leaves the global economic outlook more uncertain over the coming period. The Jordanian economy is also hit hard by the pandemic amidst already high unemploymentand debt levels. Prior to the COVID-19 shock, for the past four years the economy was growing at a low trajectory of around 2.0 percent. This rate of growth was insufficient to absorb the country’s young and growing labor force. These challenges have now been exacerbated by COVID-19 related economic disruptions. Jordan’s unemployment rate spiked to 23.0 percent in Q2-2020, 3.7 percent higher than Q1-2020, with youth, particularly female youth, disproportionally affected by the crisis. Moreover, according to a World Bank study on the short-term impact of the COVID-19 pandemic on businesses, Jordan is among the countries with the largest expected drop in sales, at 60 percent, while 54 percent of businesses report they have fallen or expect to fall in arrears.